Semantic Transformations of Word bomb and Its Derivatives as a Reflection of Shifts in the Linguistic Picture of World - E. A. Kitanina; D. S. Trukhanova (Научный диалог, 2020)
The authors determine their values on the basis of the analysis of a wide range of lexicographic sources and the most frequency contexts for the use of the units in question, extracted from texts functioning in real and virtual communication. In addition, the authors turn to sociolinguistic research methods. It is shown that individual units and new meanings are poorly represented in lexicography. Cases of transformation of the connotative halo of the words under consideration are noted. It is shown that the analyzed units are characterized by diffuse semantics, wide compatibility and expressiveness, which determines their high pragmatic potential and, as a result, the high frequency of use in media texts. The authors devote considerable attention to the question of the possible reasons for the development of new semantics among the derivatives of the word bomb , considering them as a result of the influence of Anglo-American linguistic culture. Questions on the perception of new tokens by native speakers and the advisability of using these language units in different communicative situations are also raised. The analysis allows us to identify some trends in the transformation of the Russian linguistic picture of the world in the context of global processes that affect the development of Russian linguistic culture.